2013
DOI: 10.7861/clinmedicine.13-5-482
|View full text |Cite
|
Sign up to set email alerts
|

Coming of age in cystic fibrosis – transition from paediatric to adult care

Abstract: -Cystic fibrosis (CF) is the most common multisystem inherited disorder, with a UK population exceeding 9,000. There have been significant improvements in CF survival over the decades, attributed to improvements in therapies available, our understanding of the disease and better organisation of care. CF care providers have been early advocates for successful healthcare transition from the paediatric to adult sector and CF can be considered a model process where a paediatric disease has now become an adult one.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
(18 reference statements)
0
20
0
1
Order By: Relevance
“…This model is now commonly used in CF services and it allows the young person and parents to become familiar with the adult service. 19 Successful transition must address the views, concerns and expectations of young people and their parents, and must be adapted to individual circumstances, such as care transferring from a local paediatric unit to a regional adult centre. 20 People with long-term conditions exhibit a variety of coping strategies that maintain their psychological health but also influence their adherence to treatments.…”
Section: Discussionmentioning
confidence: 99%
“…This model is now commonly used in CF services and it allows the young person and parents to become familiar with the adult service. 19 Successful transition must address the views, concerns and expectations of young people and their parents, and must be adapted to individual circumstances, such as care transferring from a local paediatric unit to a regional adult centre. 20 People with long-term conditions exhibit a variety of coping strategies that maintain their psychological health but also influence their adherence to treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Cystic fibrosis shares many features with PCD including the need for intensive physiotherapy and antibiotics. Life expectancy in cystic fibrosis patients has increased over recent decades and it has changed from a predominantly paediatric disease to an adult one [23]. Models of transitional care for cystic fibrosis might inform PCD care; the need for collaborative working between paediatric and adult clinics is essential to enable longitudinal understanding of the patient "from cradle to grave".…”
Section: Transition From Paediatric To Adult Carementioning
confidence: 99%
“…A cohort of previous studies recognised future plans, careers, reproduction, genetics, adolescent relationships and behaviour as important key items in developing a structured programme (Brumfield & Lansbury, ; Duguépéroux et al., ; Nazareth & Walshaw, ). This was evident by all participants in this research who also felt these were all important but interestingly, future plans were deemed the most important.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies identified information, education and training with emphasis on adolescent behaviour as key issues prior to transition (Al-Yateem, 2013;Brumfield & Lansbury, 2004;Flume, Taylor, Anderson, Gray, & Turner, 2004;Begley, 2013). A cohort of studies strongly recommended developing individual CF programmes done in collaboration with adolescents taking into account developmental readiness, maturity and identifying future plans such as careers, fertility and relationships (Brumfield & Lansbury, 2004;Dugu ep eroux et al, 2008;Nazareth & Walshaw, 2013). Poor knowledge and understanding of reproduction and genetics were highlighted in a study carried out by Siklosi et al (2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation